The Relevance of Hadith 'Falyakul Khairan au Liyasmut' in Contemporary Education: Communication Ethics Strategies for Character Building in the Digital Age - Romadhon, Muhammad Qomari; Qomariyah, Nurul; Muhajirin, Muhajirin (International Journal of Education, Information Technology, and Others, 2024)
This study aims to explore the philosophical and pedagogical meanings of the hadith “Falyakul Khairan au Liyasmut” in the context of modern education, especially related to the formation of communication ethics and the character of students in the digital era. The research uses a literature study method with qualitative analysis involving primary sources such as classical books of hadith and tafsir, as well as secondary sources such as journals and thematic books. The results show that this hadith has deep meaning in three main aspects: ontological (the nature of speech), axiological (ethical values), and methodological (ways of communication). In education, the implementation of this hadith includes reconstructing the hidden curriculum, developing communication ethics modules, reflective methods, and holistic assessments. The research also highlights the relevance of the hadith in three dimensions: philosophical, pedagogical and digital. The hadith is able to direct communication to be more reflective, meaningful and ethical, and supports the development of emotional intelligence and empathy. The hadith principle does not limit expression but encourages awareness and moral responsibility in communication.